Effective reading - Greenall, Simon (Cambridge University Press, 1986)
Effective Reading provides a wide variety of interesting, up-to-date reading material with challenging and motivating exercises which develop the relevant skills. All the texts are authentic and come from many different sources including contemporary British and American novels, newspapers, magazines and advertising. Each unit contains one or two reading passages, four or five skills exercises, and suggestions for further work.